POPULAR KNOWLEDGE AND CULTURES: DIALOGUES BETWEEN EXPERIENCES AND ECOLOGY OF KNOWLEDGE IN THE ZONA DA MATA OF MINAS GERAIS - da Fonseca , Valter Machado; Silva, Carmen Lucia Ferreira (Seven Editora, 2024)
In this research, the authors discuss some foundations, assumptions, principles and concepts that are important for working with Popular Education. They examine the basic concepts of culture, correlating them with the need to value the knowledge produced by the marginalized sectors of modern society. In this text, the authors show that working with the most diverse forms of cultures demands giving up dogmatic conceptions, precisely because they understand the concept of culture inserted in a spontaneous and free historical and social context, where social actors build their cultural identity independent of the cultural conceptions and concepts imposed by the State and by the economic elites that hold political and economic power that govern modern society. It makes a distinction between the knowledge coming from the popular sectors and those produced by the capitalist State and reproduced by formal education. Finally, the article presents aspects and records of the richness of cultural dialogues of the "Exchange of Knowledge", an event held at UFV.DOI: https://doi.org/10.56238/sevened2024.037-077